2016
DOI: 10.1186/s40064-016-3088-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism rather than obesity is associated with ischemic stroke: a cross-sectional study in rural Northeastern China

Abstract: Little is known about stroke with different obesity phenotype as determined using the Adult Treatment Panel-III criteria with metabolic health or not. This study aimed to investigate the effects of metabolically healthy and unhealthy obesity on ischemic stroke in a general population. A total of 11,150 adults were examined using a multi-stage cluster sampling method to select a representative sample of individuals 35 years or older. Ischemic stroke was defined as history of a cerebrovascular event, as document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
0
11
0
2
Order By: Relevance
“…12,13,16 Penelitian yang dilakukan oleh Schmiegelow et al (2015) menunjukkan bahwa komponen sindrom metabolik lainnya seperti hipertensi, diabetes melitus, dan dislipidemia lebih memiliki keterkaitan dengan risiko penyakit kardiovaskular dibandingkan obesitas. 17 Penelitian yang dilakukan oleh Li et al (2016) menunjukkan bahwa individu yang mengalami obesitas tanpa adanya komponen sindrom metabolik lainnya tidak memiliki kerterkaitan dengan peningkatan probabilitas stroke iskemik. Pada penelitian tersebut, individu yang mengalami obesitas disertai adanya komponen sindrom metabolik lainnya dan individu tanpa obesitas disertai adanya komponen sindrom metabolik lainnya memiliki keterkaitan dengan peningkatan probabilitas stroke iskemik.…”
Section: Probabilitas Stroke Iskemik Menurut Framingham Studyunclassified
See 1 more Smart Citation
“…12,13,16 Penelitian yang dilakukan oleh Schmiegelow et al (2015) menunjukkan bahwa komponen sindrom metabolik lainnya seperti hipertensi, diabetes melitus, dan dislipidemia lebih memiliki keterkaitan dengan risiko penyakit kardiovaskular dibandingkan obesitas. 17 Penelitian yang dilakukan oleh Li et al (2016) menunjukkan bahwa individu yang mengalami obesitas tanpa adanya komponen sindrom metabolik lainnya tidak memiliki kerterkaitan dengan peningkatan probabilitas stroke iskemik. Pada penelitian tersebut, individu yang mengalami obesitas disertai adanya komponen sindrom metabolik lainnya dan individu tanpa obesitas disertai adanya komponen sindrom metabolik lainnya memiliki keterkaitan dengan peningkatan probabilitas stroke iskemik.…”
Section: Probabilitas Stroke Iskemik Menurut Framingham Studyunclassified
“…Hal ini menunjukkan bahwa sindrom metabolik lebih memiliki keterkaitan dengan peningkatan probabilitas stroke iskemik, dibandigkan dengan obesitas. 18 Seperti yang telah diuraikan sebelumnya, Lu et al (2006) yang menyatakan bahwa RLPP memiliki korelasi signifikan dengan probabilitas terjadinya stroke iskemik. 13 Hal tersebut tidak sesuai dengan hasil analisis pada penelitian ini.…”
Section: Probabilitas Stroke Iskemik Menurut Framingham Studyunclassified
“…Metabolic syndrome (MetS) as an integrated statue of metabolic disorders-elevated plasma glycemia, central obesity, hypertension and dyslipidemia, is an important predictor of recurrent stroke, with 52% increased risk of recurrent stroke 7 . However, among the components of Mets, obesity illustrates lower in uence than the other risk factors, no matter on stroke 8 or recurrent stroke 9,10 . Concretely, a metaanalysis of cohort studies showed that the hazard ratio of obesity for recurrent stroke was 1.12 (0.89-1.41), signi cantly lower than that of elevated glycemia and dyslipidemia 9 .…”
Section: Introductionmentioning
confidence: 98%
“…Whether or not recurrent stroke is more likely related to poor metabolic health rather than to obesity remains uncertain, while con icting data are similarly examined among the new-onset stroke. Previous studies reported that obese individuals with otherwise metabolically healthy pro le, referred as "metabolically healthy obesity (MHO)", did not have increased risk of stroke than metabolically healthy non-obesity 10 . However, apparent lean but metabolically unhealthy experienced higher risk of stroke, and the risk increased as the number of metabolic syndrome components increased 12 .…”
Section: Introductionmentioning
confidence: 99%
“…abdominal type of obesity, IR, impaired fasting glucose / glucose tolerance, and low level of cardiorespiratory fitness, is considered plenty acceptable criteria of metabolically healthy obese [4]. Thus, there are at least two main body-size phenotypes (metabolically healthy and metabolically non-healthy) of individuals with established obesity [5], but the cardiometabolic risk amongst these patients' populations extremely distinguishes [6].…”
mentioning
confidence: 99%